Learning Design of Pythagorean Theorem Contextualized Salt House with Interactive Videos - Eka Rahmawati; Farida Nursyahidah; Irkham Ulil Albab (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2023)
The Pythagorean theorem is one of the materials in geometry and has a close relationship with everyday life. However, many students still have difficulty understanding the concepts and solving problems related to the material. This study aims to develop a learning trajectory that assists students in improving their ability to understand the concept of the Pythagorean theorem using the context of an interactive video-assisted Salt House in class VII SMP Negeri 2 Pegandon. This learning trajectory consists of four activities, namely: (1) finding the concept and formula of the Pythagorean theorem with the help of a video context; (2) finding concepts related to the length of one side of a triangle if two sides are known; (3) determining the type of triangle based on the length of its side; (4) finding and checking related Pythagorean triple number patterns. This study uses design research method which consists of three stages, namely preparing for the experiment, design experiment, and retrospective analysis. The learning approach used is PMRI. The results of the research conducted show that the learning trajectory obtained can improve students' mathematical problem solvings skills on the Pythagorean theorem material